Correction: The use of a single-crystal nickel-rich layered NCM cathode for excellent cycle performance of lithium-ion batteries. (11th March 2021) - Guo, Qiankun; Huang, Jili; Liang, Zhao; Potapenko, Hanna; Zhou, Miaomiao; Tang, Xiaodong; Zhong, Shengwen
Abstract : Correction for 'The use of a single-crystal nickel-rich layered NCM cathode for excellent cycle performance of lithium-ion batteries' by Qiankun Guo et al., New J. Chem., 2021, 45, 3652–3659; DOI: ; 10.1039/d0nj05914e .